Environment-friendly marine biofouling resistant coating and preparation method thereof

CN122790518APending Publication Date: 2026-09-22ZHUHAI LANLUO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611194422.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0004]但是,现有环保型防污涂层在长期使用过程中仍存在防海生物附着性能难以稳定保持的问题

Benefits of technology

本发明中,通过在双组分聚脲体系中引入端氨基聚硅氧烷,使端氨基聚硅氧烷中的端氨基能够与异氰酸酯基发生反应,并使聚硅氧烷链段通过脲键连接于聚脲交联网络中。聚硅氧烷链段在涂层固化过程中能够向涂层表层适度富集,从而形成较稳定的低表面能区域,降低海洋微生物分泌物、海藻附着物及海洋生物幼体与涂层表面之间的结合强度。与直接加入非反应型硅油相比,端氨基聚硅氧烷能够通过化学反应固定于聚脲网络中,减少长期海水浸泡及水流冲刷过程中发生迁移和流失的可能性,有利于保持涂层长期的低表面能性能,并使已经附着于涂层表面的海洋污损物更容易在水流剪切或清洗作用下脱离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an environment-friendly coating capable of preventing marine bio-attachment and a preparation method thereof, and belongs to the technical field of marine protective coating. The coating comprises A component and B component which are stored independently. The A component comprises isocyanate-terminated polyether prepolymer and isocyanate trimer. The B component comprises amino-terminated polyether, aromatic diamine chain extender, amino-terminated polysiloxane, capsaicin slow-release particles, inorganic reinforcing filler and functional additives. After the A component and the B component are mixed, a polyurea crosslinking network is formed. The amino-terminated polysiloxane is fixed to the polyurea crosslinking network through a urea bond and forms a low-surface-energy area on the surface layer of the coating. The capsaicin slow-release particles continuously release capsaicin in a seawater environment. Through the synergistic effect of low-surface-energy desorption and slow-release inhibition of natural active substances, the initial attachment tendency of marine organisms and the bonding strength of the attached pollutants are reduced on the basis of maintaining the elasticity, impact resistance, wear resistance and seawater resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine protective coating technology, and in particular to an environmentally friendly coating that prevents marine organism attachment and its preparation method. Background Technology

[0002] Marine vessels, offshore platforms, port facilities, seawater pipelines, marine buoys, marine aquaculture equipment, and other engineering facilities that are in long-term contact with seawater are susceptible to the adhesion of algae, bacteria, barnacles, shellfish, and other marine organisms during use. After continuous attachment and reproduction on the surface of these facilities, marine organisms gradually form a biofouling layer of considerable thickness. This not only increases the roughness of the hull or marine equipment surface and operational resistance, leading to increased energy consumption, but also easily causes changes in local water flow conditions and allows corrosive media to remain on the surface for extended periods, thus accelerating the corrosion and aging of marine facilities. To reduce the impact of marine organism attachment on marine engineering facilities, it is usually necessary to apply an anti-biofouling coating to the outer surface of the facilities. This coating isolates seawater from the substrate while reducing the colonization and growth of marine microorganisms, algae, and large marine organisms on the facility surface.

[0003] Existing antifouling coatings mainly include copper-containing antifouling coatings, self-polishing antifouling coatings, and low-surface-energy environmentally friendly antifouling coatings. Copper-containing antifouling coatings typically utilize the continuous release of cuprous oxide or other copper-containing antifouling components in seawater to inhibit marine organisms. Self-polishing antifouling coatings, through resin hydrolysis in seawater or continuous surface renewal, allow already attached or soon-to-attach marine organisms to gradually detach from the coating surface. With increasingly stringent requirements for marine environmental protection, some environmentally friendly antifouling coatings use polyurethane, polyurea, or silicone materials to form a continuous protective film, utilizing the coating's smooth surface, hydrophobicity, and low surface energy to reduce the bonding strength between marine organism secretions and the coating. To further enhance antifouling performance, some coatings also directly incorporate capsaicin, plant extracts, or other natural antifouling ingredients, allowing these natural active substances to be gradually released in the seawater environment, reducing the tendency of bacteria, algae, and marine larvae to attach to the coating surface.

[0004] However, existing environmentally friendly antifouling coatings still suffer from the problem of unstable antifouling performance during long-term use. This is because relying solely on the smooth, hydrophobic properties of silicone materials or the coating surface primarily reduces the bonding strength between existing marine fouling and the coating. Under conditions of prolonged ship berthing, low seawater flow, or lack of external water shear, bacteria and microalgae can still gradually form an initial biofilm on the coating surface. This biofilm then provides a substrate for the attachment of algae, barnacles, and shellfish larvae. Furthermore, directly adding chili powder, free capsaicin, or plant extracts to the coating can lead to variations in the active ingredient content between different batches due to the influence of raw material variety, origin, and processing conditions. Free active ingredients tend to migrate and release rapidly in the initial stages of seawater application, resulting in a large initial release. As the surface active ingredients are gradually consumed, it becomes difficult to maintain an effective antifouling effect. In addition, silicone components that have not formed a stable bond with the coating substrate may migrate or be lost during long-term seawater immersion and water erosion, causing a gradual decline in the low surface energy properties of the coating surface. Therefore, how to maintain the coating's resistance to seawater, impact, and abrasion while ensuring the long-term stability of its low surface energy function and the slow-release function of natural active substances, thereby improving the long-term anti-marine organism adhesion performance of environmentally friendly coatings, has become a technical problem that needs to be solved. Summary of the Invention

[0005] The purpose of this invention is to provide an environmentally friendly coating that prevents marine organisms from attaching, and a method for preparing the same, in order to solve the above-mentioned problems.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: An environmentally friendly coating that prevents marine organism attachment includes two independently stored components, A and B; component A comprises an isocyanate-terminated polyether prepolymer and an isocyanate trimer. Component B comprises difunctional amino-terminated polyether, trifunctional amino-terminated polyether, aromatic diamine chain extender, amino-terminated polysiloxane, capsaicin sustained-release particles, inorganic reinforcing filler, and functional additives; the capsaicin sustained-release particles comprise porous silica, capsaicin loaded within the pores of the porous silica, and an ethyl cellulose sustained-release layer coating the outside of the capsaicin-loaded porous silica. After the components A and B are mixed and cured, a polyurea crosslinking network is formed. The terminal amino groups in the terminal amino polysiloxane react with the isocyanate groups in the component A, so that the polysiloxane segments are linked to the polyurea crosslinking network through urea bonds, and a low surface energy region containing polysiloxane segments is formed on the coating surface. The capsaicin slow-release particles are dispersed in the polyurea crosslinking network, and the capsaicin is released slowly through the porous silica and ethyl cellulose slow-release layer.

[0007] In one embodiment, based on a total mass of 100 parts for component A, component A comprises 78-88 parts of isocyanate-terminated polyether prepolymer and 12-22 parts of hexamethylene diisocyanate trimer; based on a total mass of 100 parts for component B, component B comprises 40-46 parts of difunctional amino-terminated polyether, 4-8 parts of trifunctional amino-terminated polyether, 22-28 parts of aromatic diamine chain extender, 6-10 parts of amino-terminated polysiloxane, 4-8 parts of capsaicin sustained-release granules, 4-8 parts of rutile titanium dioxide, 1-2.5 parts of hydrophobic fumed silica, 0.5-1.5 parts of ultraviolet absorber, 0.3-1.0 parts of hindered amine light stabilizer, 0.5-1.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.2-0.6 parts of leveling agent, and 0.5-1.5 parts of activated 3A molecular sieve powder.

[0008] In one embodiment, the isocyanate-terminated polyether prepolymer is an aliphatic isocyanate-terminated polyether prepolymer, and the isocyanate group mass content of the aliphatic isocyanate-terminated polyether prepolymer is 10.5% to 12.5%; the isocyanate trimer is a hexamethylene diisocyanate trimer, and the isocyanate group mass content of the hexamethylene diisocyanate trimer is 21% to 23%; and the isocyanate group mass content of component A is 13.2% to 14.0%.

[0009] In one embodiment, the terminal amino polysiloxane is α,ω-diaminopropyl-terminated polydimethylsiloxane, the number-average molecular weight of the terminal amino polysiloxane is 1500-3000, and the amine value is 35-70 mgKOH / g; the terminal amino polysiloxane reacts with isocyanate groups at both ends of its amino groups to fix the polysiloxane segments in the polyurea crosslinking network.

[0010] In one embodiment, based on the total mass of the capsaicin sustained-release particles, the capsaicin sustained-release particles comprise 25%–35% capsaicin, 55%–65% porous silica, and 8%–12% ethyl cellulose; the capsaicin has a mass purity of not less than 95%, the porous silica has an average particle size of 5–15 μm, and the capsaicin sustained-release particles have a particle size of 5–20 μm.

[0011] In one embodiment, the difunctional terminal amino polyether has a number-average molecular weight of 1800-2200 and an amine functionality of 2; the trifunctional terminal amino polyether has a number-average molecular weight of 4500-5500 and an amine functionality of 3; the aromatic diamine chain extender is diethyltoluene diamine; and the inorganic reinforcing filler includes surface-treated rutile titanium dioxide and hydrophobically treated fumed silica with organosilane.

[0012] In one embodiment, the isocyanate index of the mixture of component A and component B is 1.00 to 1.08; the cured coating includes a polyurea host layer connected to the substrate and a low surface energy functional region formed on the outside of the polyurea host layer, the capsaicin slow-release particles are dispersed in the polyurea host layer, and at least a portion of the capsaicin slow-release particles are located on the side close to the low surface energy functional region.

[0013] This application also provides a method for preparing an environmentally friendly coating that prevents marine organism attachment, including the following steps: S1. The isocyanate-terminated polyether prepolymer is added to the reaction equipment, heated and stirred under nitrogen protection, the isocyanate trimer is added, and after mixing, vacuum degassing and filtration are performed to obtain component A. S2. Vacuum dehydrate the difunctional amino-terminated polyether and the trifunctional amino-terminated polyether, mix the dehydrated difunctional amino-terminated polyether and trifunctional amino-terminated polyether, and add amino-terminated polysiloxane. S3. Add dispersant, rutile titanium dioxide and hydrophobic fumed silica to the mixture obtained in step S2, and disperse at high speed. S4. Reduce the temperature and dispersion speed of the material obtained in step S3, add capsaicin slow-release granules and disperse at low speed. S5. Add aromatic diamine chain extender, ultraviolet absorber, hindered amine light stabilizer, defoamer, leveling agent and activated 3A molecular sieve powder, mix, vacuum degas, filter and seal and fill to obtain component B; S6. Mix the components A and B and spray them onto the surface of the substrate. After curing, the environmentally friendly coating that prevents marine organisms from adhering is formed.

[0014] In one embodiment, the preparation method of the capsaicin sustained-release particles includes the following steps: dissolving capsaicin in ethanol, adding porous silica and pre-dispersing it; placing the mixture containing capsaicin and porous silica under a vacuum of -0.08 to -0.095 MPa for 20 to 40 minutes, releasing the vacuum and continuing to stir to allow capsaicin to enter and adsorb into the internal pores of the porous silica; removing ethanol under reduced pressure at 45 to 55°C to obtain capsaicin-loaded porous silica; dissolving ethyl cellulose in an organic solvent to form an ethyl cellulose coating solution; spraying the ethyl cellulose coating solution onto the surface of the capsaicin-loaded porous silica, and after mixing, vacuum drying and sieving, obtaining the capsaicin sustained-release particles.

[0015] In one embodiment, in step S6, the substrate is sandblasted to remove rust, achieving a surface cleanliness of Sa2.5, and an epoxy primer layer with a dry film thickness of 100–150 μm is formed on the substrate surface. Component A is heated to 65–75°C, and component B is heated to 60–70°C. The coating is then applied using a two-component high-pressure spraying device at a spraying pressure of 14–20 MPa, with a volume ratio of component A to component B of 1:1 ± 0.03. The resulting polyurea functional coating has a dry film thickness of 1.5–3.0 mm and is cured at 20–30°C for 24–36 hours.

[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: In this invention, by introducing amino-terminated polysiloxanes into a two-component polyurea system, the amino groups in the amino-terminated polysiloxanes can react with isocyanate groups, and the polysiloxane segments are linked to the polyurea crosslinking network via urea bonds. During coating curing, the polysiloxane segments can moderately accumulate on the coating surface, forming a more stable low surface energy region, reducing the bonding strength between marine microbial secretions, algae attachments, and marine larvae and the coating surface. Compared to directly adding non-reactive silicone oil, amino-terminated polysiloxanes can be chemically fixed in the polyurea network, reducing the possibility of migration and loss during long-term seawater immersion and water flow scouring. This helps maintain the long-term low surface energy performance of the coating and makes it easier for marine fouling substances already attached to the coating surface to detach under the shearing or washing action of water flow.

[0017] This invention utilizes porous silica to support capsaicin, and forms an ethyl cellulose slow-release layer on the outside of the capsaicin-loaded porous silica. This allows capsaicin to be stored within the internal pores of the porous silica, and the migration path of capsaicin to the coating surface is prolonged through the porous carrier and the ethyl cellulose slow-release layer. This structure reduces the concentrated release of capsaicin during the initial application of the coating in seawater, allowing capsaicin to gradually act on the interface between the coating and seawater over a longer period, thereby reducing the initial attachment tendency of bacterial biofilms, algal spores, and marine larvae. Simultaneously, replacing ordinary chili powder with capsaicin of a defined content reduces the impact of plant fibers and coarse particles on the coating smoothness and spraying process, and improves the consistency of components and the reproducibility of preparation between different production batches.

[0018] This invention uses a polyurea crosslinked network as the continuous support structure of the coating, and forms flexible segments through difunctional terminal amino polyethers and branched crosslinked structures through trifunctional terminal amino polyethers and isocyanate trimers. This gives the coating good elasticity, impact resistance, abrasion resistance, and seawater stability. Hydrophobic fumed silica further improves the coating's anti-sagging, abrasion resistance, and scratch resistance. The continuous polyurea phase can encapsulate and fix terminal amino polysiloxanes and capsaicin slow-release particles, allowing the low surface energy desorption effect to work in conjunction with the slow-release inhibition effect of natural active substances. While maintaining the mechanical protective performance of the coating, it also reduces the initial attachment tendency of marine organisms and the binding strength of already attached fouling substances. In addition, this invention does not use heavy metal-releasing antifouling components such as cuprous oxide and organotin compounds, which helps to reduce the risk of pollution to the marine environment caused by the long-term use of traditional release-type antifouling coatings. Detailed Implementation

[0019] The following detailed description, through specific embodiments, illustrates an environmentally friendly coating that prevents marine organism adhesion and its preparation method, provided by the present invention. It should be understood that the following embodiments are merely illustrative of the technical solution of the present invention and are not intended to limit the scope of protection of the present invention. Reasonable adjustments or equivalent substitutions made by those skilled in the art to the component dosage and process parameters based on actual production equipment, construction environment, and coating usage requirements, without departing from the technical concept of the present invention, should all be included within the scope of protection of the present invention.

[0020] Unless otherwise specified, the amount of each raw material used in this embodiment is expressed in parts by weight.

[0021] The environmentally friendly, anti-marine organism coating provided by this invention is a solvent-free two-component polyurea coating, comprising independently stored component A and component B. Component A is a reactive component containing isocyanate groups, mainly used to form the hard segment structure and cross-linking structure of the polyurea coating; component B is a resin component containing amino-active hydrogen and contains reactive terminal amino polysiloxane, capsaicin slow-release particles, inorganic reinforcing materials, and functional additives.

[0022] During application, components A and B are added separately to a two-component high-pressure spraying device and mixed according to the equivalence relationship between isocyanate groups and amino active hydrogen, so that the isocyanate index is controlled at 1.00-1.08, preferably 1.02-1.06. By controlling the content of isocyanate groups in component A and the amine value of component B, the actual spray volume ratio of components A and B is controlled at 1:1 ± 0.03.

[0023] After components A and B enter the mixing chamber of the spray gun, the isocyanate groups in component A react rapidly with the amino groups in difunctional amino-terminated polyether, trifunctional amino-terminated polyether, diethyltoluenediamine, and amino-terminated polysiloxane, respectively, and form a continuous and dense polyurea crosslinked structure on the substrate surface.

[0024] The cured coating uses a polyurea crosslinked network as the continuous phase, with terminal amino polysiloxanes linked to the network via urea bonds. During curing, these polysiloxanes moderately accumulate on the outer surface of the coating to form low surface energy regions containing polysiloxane segments. Capsaicin slow-release particles are uniformly dispersed in the polyurea continuous phase, with some particles distributed near the outer surface of the coating, slowly releasing capsaicin during seawater immersion.

[0025] The low surface energy regions formed by amino-terminated polysiloxanes primarily reduce the adhesion strength of marine microbial secretions, algal attachments, and marine larvae to the coating surface, making them easier to detach under seawater flow, ship movement, or low-intensity cleaning. Capsaicin slow-release particles mainly reduce the initial colonization tendency of bacterial biofilms, algal spores, and marine larvae on the coating surface. Both act on different stages of the marine organism attachment process, thus forming a synergistic antifouling effect combining low surface energy desorption and natural active substance inhibition.

[0026] Main raw materials The isocyanate group mass content of the aliphatic isocyanate-terminated polyether prepolymer used in this embodiment is 10.5% to 12.5%, preferably 11.5%, and its viscosity at 25°C is 800 to 1500 mPa·s.

[0027] The isocyanate group content of the hexamethylene diisocyanate trimer is 21% to 23%, preferably 22%.

[0028] The number-average molecular weight of difunctional amino-terminated polyethers is 1800–2200, and the amine functionality is 2. Difunctional amino-terminated polyethers are used to form flexible polyether segments within polyurea coatings to improve the coating's elasticity, impact resistance, and low-temperature flexibility.

[0029] The trifunctional amino-terminated polyether has a number-average molecular weight of 4500–5500 and an amine functionality of 3. It is used to form branched cross-linked structures in the polyurea continuous phase to improve the overall strength of the coating and enhance the coating and fixation effect of the polyurea matrix on capsaicin sustained-release particles.

[0030] The chain extender used is diethyltoluene diamine. Diethyltoluene diamine can improve the reaction rate and hard segment content of polyurea coatings, enabling the coating to maintain good wear resistance and seawater resistance while curing rapidly.

[0031] The amino-terminated polysiloxane is α,ω-diaminopropyl-terminated polydimethylsiloxane, with a number-average molecular weight of 1500–3000, preferably 1800–2500, and an amine value of 35–70 mg KOH / g. The terminal amino groups in the amino-terminated polysiloxane can react with isocyanate groups, allowing the polysiloxane segments to be chemically bonded to the polyurea crosslinking network. Compared to ordinary non-reactive silicone oils, the amino-terminated polysiloxane is less likely to migrate and bleed from the polyurea coating during long-term seawater immersion, which is beneficial for improving the long-term stability of the coating's low surface energy properties.

[0032] Capsaicin is produced using capsaicin raw materials with a capsaicin content of no less than 95%. Using pure capsaicin or capsaicin raw materials with clearly defined content can avoid fluctuations in the effective components caused by differences in chili varieties, origins, and plant fiber content when using chili powder directly.

[0033] Porous silica has an average particle size of 5–15 μm and a specific surface area of ​​200–500 m² / g. It is used to load capsaicin and extend the migration path of capsaicin from the interior of the particles to the exterior of the coating.

[0034] The ethoxy content of ethyl cellulose is 45%–49% by mass. Ethyl cellulose is used to form a slow-release layer with a microporous structure on the outside of porous silica loaded with capsaicin, so as to reduce the rate at which seawater enters the pores of the carrier and reduce the concentrated release of capsaicin in the early stage of use.

[0035] Rutile titanium dioxide is produced by surface treatment with alumina and organic materials, with an average particle size of 0.2–0.4 μm. Rutile titanium dioxide is used to improve the hiding power, weather resistance, and UV aging resistance of coatings.

[0036] Hydrophobic fumed silica is made from fumed silica surface-treated with organosilane. Hydrophobic fumed silica can improve the thixotropic properties, anti-sagging properties, abrasion resistance, and scratch resistance of the coating.

[0037] The UV absorber is a hydroxyphenylbenzotriazole UV absorber, the hindered amine light stabilizer is a low-alkaline hindered amine light stabilizer, the dispersant is a polymer-type wetting and dispersing agent that does not contain active hydrogen, the defoamer is a silicone-free polymer defoamer, and the leveling agent is a polyether-modified silicone leveling agent.

[0038] The molecular sieve uses activated 3A molecular sieve powder with an average particle size of 2-10 μm to adsorb trace amounts of moisture in component B, reducing the possibility of trace amounts of moisture reacting with isocyanate groups to generate carbon dioxide bubbles.

[0039] Preparation of capsaicin sustained-release granules Weigh out 30 parts capsaicin, 60 parts porous silica and 10 parts ethyl cellulose.

[0040] First, add 30 parts capsaicin to 270 parts anhydrous ethanol, heat the mixture to 40°C, and stir at 400 r / min for 20 min to fully dissolve the capsaicin, thus obtaining a capsaicin ethanol solution.

[0041] Sixty parts of porous silica were added to the capsaicin ethanol solution and pre-dispersed at a speed of 500 r / min for 15 min to ensure that the porous silica was uniformly suspended in the capsaicin ethanol solution.

[0042] The mixture was transferred to a vacuum impregnation apparatus, the vacuum was reduced to -0.09 MPa and maintained for 30 minutes to allow the air in the pores of the porous silica to be fully expelled.

[0043] After the vacuum holding period ended, the vacuum was slowly released, allowing the internal pressure of the vacuum impregnation equipment to return to atmospheric pressure. During the pressure recovery process, the capsaicin ethanol solution entered the internal pores of the porous silica. After the vacuum was released, stirring was continued at 400 rpm for 45 minutes to ensure that capsaicin was fully adsorbed into the internal pores and particle surface of the porous silica.

[0044] The mixture was transferred to a vacuum evaporator and ethanol was recovered under conditions of 45–50 °C and a vacuum of -0.08 MPa until the mixture formed a free-flowing powder, yielding porous silica loaded with capsaicin.

[0045] Take another 10 parts of ethyl cellulose and add it to a mixed solvent composed of ethanol and ethyl acetate. The mass ratio of ethanol to ethyl acetate is 3:7. This allows the ethyl cellulose to be fully dissolved, and a coating solution with a mass concentration of 8% ethyl cellulose is prepared.

[0046] The capsaicin-loaded porous silica was added to a mixing device equipped with a stirrer and a spraying device, and stirred at a speed of 400 r / min. While maintaining stirring, the ethyl cellulose coating solution was sprayed evenly onto the capsaicin-loaded porous silica surface at a speed of 4-6 mL / min.

[0047] After the coating solution is sprayed, continue stirring at 400 r / min for 30 min to form an incompletely closed sustained-release layer on the outside of the capsaicin-loaded porous silica, with continuous coating areas and microporous areas distributed among them.

[0048] The coated granules were placed in a vacuum drying apparatus and dried for 6 hours at 45°C and a vacuum of -0.09 MPa to reduce the residual solvent content in the granules to below 0.5%. The dried granules were then sieved to obtain capsaicin sustained-release granules with a particle size mainly distributed in the range of 5–20 μm.

[0049] The capsaicin sustained-release granules obtained contain approximately 30% capsaicin by mass, approximately 60% porous silica by mass, and approximately 10% ethyl cellulose by mass.

[0050] Using the above preparation method, capsaicin is adsorbed and stored in the internal pores of porous silica, which increases the migration path length of capsaicin from the inside of the particles to the outside. Ethyl cellulose is formed on the outside of the carrier, constituting a diffusion barrier layer with a microporous structure. After the coating is introduced into a seawater environment, seawater gradually enters the porous silica through the micropores in the ethyl cellulose slow-release layer, causing capsaicin to slowly migrate to the interface between the polyurea coating and seawater, thereby reducing the problem of concentrated release of capsaicin in the early stages of coating use.

[0051] Compared to adding regular chili powder directly, using capsaicin slow-release granules avoids increasing the surface roughness of the coating due to plant fibers and coarse particles, and reduces the possibility of plant fibers clogging the spraying equipment. At the same time, using slow-release granules with a clearly defined capsaicin content helps improve the consistency of components and the stability of antifouling performance between different production batches.

[0052] Preparation of component A Weigh out 82 parts of aliphatic isocyanate-terminated polyether prepolymer and 18 parts of hexamethylene diisocyanate trimer.

[0053] Dry nitrogen is continuously introduced into the reactor equipped with a stirring device, a heating device, and a nitrogen protection device to replace the air and moisture inside the reactor.

[0054] Add 82 parts of aliphatic isocyanate-terminated polyether prepolymer to the reactor and raise the material temperature to 50°C. Turn on the agitator and stir at 300 rpm.

[0055] Under nitrogen protection and stirring conditions, 18 parts of hexamethylene diisocyanate trimer were slowly added to the reactor, with the addition time controlled at 10-15 minutes.

[0056] After the hexamethylene diisocyanate trimer is added, the material temperature is maintained at 50±3℃, and stirring is continued at 300r / min for 45min to ensure that the aliphatic isocyanate-terminated polyether prepolymer and the hexamethylene diisocyanate trimer are fully mixed.

[0057] After mixing, the isocyanate group content in component A was measured, and the isocyanate group mass content was controlled at 13.2%–14.0%. The mixed component A was then degassed for 15 minutes under a vacuum of -0.08 MPa.

[0058] After degassing, the vacuum is released using dry nitrogen, and component A is filtered through a 100-mesh filter. The filtered component A is then filled into a sealed packaging container, and dry nitrogen is introduced into the top space of the container to isolate component A from moisture in the air. The moisture content of the obtained component A is no higher than 0.05% by mass.

[0059] Aliphatic isocyanate-terminated polyether prepolymers can form flexible polyether segments in polyurea coatings, enabling the coating to undergo elastic deformation under wave impact, ship vibration, and localized collisions, and recover after the external force is removed. Hexamethylene diisocyanate trimers can increase the crosslinking density and hard segment content of the polyurea crosslinking network, thereby improving the coating's abrasion resistance, heat resistance, and seawater stability.

[0060] Example 1 This embodiment is a preferred embodiment. By weight, component B of this embodiment includes 43.0 parts of difunctional amino-terminated polyether, 6.0 parts of trifunctional amino-terminated polyether, 25.0 parts of diethyltoluene diamine, 8.0 parts of amino-terminated polysiloxane, 6.0 parts of capsaicin sustained-release granules, 6.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.2 parts of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder, totaling 100 parts by weight.

[0061] Difunctional amino-terminated polyethers and trifunctional amino-terminated polyethers were added to a vacuum dehydration device and dehydrated for 60 minutes at 80°C and a vacuum of -0.09 MPa, so that the moisture content was less than 0.05%.

[0062] 43.0 parts of dehydrated difunctional terminal amino polyether and 6.0 parts of dehydrated trifunctional terminal amino polyether were added to a dispersion vessel equipped with a stirring device, a high-speed dispersing device, a heating device, and a vacuum device. The material temperature was maintained at 70℃, and the mixture was stirred at 400 r / min for 10 min.

[0063] Add 8.0 parts of terminal amino polysiloxane to the dispersion vessel and continue stirring for 20 min at 70℃ and 400 r / min to uniformly disperse the terminal amino polysiloxane in the terminal amino polyether mixture. Add 1.2 parts of polymeric dispersant and stir at 500 r / min for 10 min.

[0064] 6.0 parts of rutile titanium dioxide and 1.5 parts of hydrophobic fumed silica were added sequentially. The speed of the high-speed dispersion device was increased to 1200 r / min, and the mixture was dispersed at high speed for 35 min at 65-70℃ to ensure that the dispersion fineness of the mixture was no greater than 30 μm.

[0065] The material temperature was reduced to 50℃, and the dispersion speed was reduced to 500 r / min. 6.0 parts of capsaicin sustained-release granules were added, and the mixture was stirred at 500 r / min for 25 min. The capsaicin sustained-release granules were added after the inorganic filler had completed high-speed dispersion to reduce the damage to the ethyl cellulose sustained-release layer caused by high-speed shear.

[0066] Continue to lower the material temperature to below 45℃, then add 25.0 parts of diethyltoluene diamine, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder in sequence, and continue stirring at a speed of 500 r / min for 30 min.

[0067] After stirring, the vacuum inside the dispersion vessel was reduced to -0.09 MPa and maintained for 20 minutes to remove air bubbles and residual moisture from the material. The vacuum was then released using dry nitrogen, and the mixture was filtered through a 120-mesh filter and sealed for filling to obtain component B of Example 1.

[0068] Ordinary carbon steel plates were selected as the test substrate. Sandblasting equipment was used to remove rust, achieving a surface cleanliness level of Sa2.5 and a surface roughness controlled between 40 and 70 μm. Oil-free compressed air was used to remove surface dust, ensuring that the substrate surface was free of oil, rust, and visible moisture.

[0069] Apply an epoxy zinc-rich thick-film primer to the carbon steel plate surface, controlling the dry film thickness to 100–120 μm. After the primer has cured and meets the recoating requirements, clean the primer surface.

[0070] Component A and Component B from Example 1 were added separately to a two-component high-pressure spraying device. Component A was heated to 70°C and Component B was heated to 65°C. The spraying pressure was controlled at 16–18 MPa. The metering pump was calibrated according to the isocyanate group content of Component A and the amine value of Component B to achieve an isocyanate index of 1.03 and to make the spraying volume ratio of Component A to Component B close to 1:1.

[0071] A polyurea functional coating is formed on the primer surface using a cross-spraying method. The wet film thickness of each spray is controlled to be 0.8–1.2 mm, resulting in a final dry film thickness of 2.0–2.5 mm. After spraying, the coating is cured for 36 hours at a temperature of 23±2℃ and a relative humidity of 50%–70%, followed by another 7 days of curing.

[0072] In Example 1, the difunctional amino-terminated polyether forms flexible polyether segments, giving the coating good elasticity and impact resistance; the trifunctional amino-terminated polyether and hexamethylene diisocyanate trimer together form a branched crosslinked structure, enabling the coating to maintain good overall strength, wear resistance and seawater stability.

[0073] The amount of amino-terminated polysiloxane added is 8.0 parts. Its amino-terminated groups participate in the polyurea curing reaction, fixing the polysiloxane segments in the polyurea crosslinking network through urea bonds, and forming a relatively stable low surface energy region on the outer surface of the coating. The amount of capsaicin slow-release particles added is 6.0 parts, forming dispersed natural active substance storage units inside the coating.

[0074] Hydrophobic fumed silica can enhance the continuous phase of polyurea and improve the wear resistance and scratch resistance of the coating, thereby reducing the wear of the low surface energy silicon-containing areas by water flow and sand particles in seawater. In Example 1, the content of terminal amino polysiloxane, capsaicin slow-release particles, degree of polyurea crosslinking, and content of inorganic reinforcing materials are matched to ensure that the coating can balance mechanical properties, long-term low surface energy performance, and slow-release performance of natural active substances.

[0075] Example 2 According to the mass fraction, component B of this embodiment includes 46.0 parts of difunctional amino-terminated polyether, 5.0 parts of trifunctional amino-terminated polyether, 26.0 parts of diethyltoluene diamine, 6.0 parts of amino-terminated polysiloxane, 4.0 parts of capsaicin sustained-release granules, 7.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.0 part of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 1.1 parts of activated 3A molecular sieve powder, with a total mass fraction of 100 parts.

[0076] The difunctional and trifunctional amino-terminated polyethers were dehydrated at 80°C and under a vacuum of -0.09 MPa for 60 min to reduce the moisture content of both amino-terminated polyethers to less than 0.05%.

[0077] 46.0 parts of dehydrated difunctional amino-terminated polyether and 5.0 parts of dehydrated trifunctional amino-terminated polyether were added to a dispersion vessel, the material temperature was controlled at 70℃, and the mixture was stirred at 400r / min for 10min.

[0078] Add 6.0 parts of amino-terminated polysiloxane and continue stirring for 20 min. Add 1.0 part of polymeric dispersant and stir for 10 min. Then add 7.0 parts of rutile titanium dioxide and 1.5 parts of hydrophobic fumed silica in sequence. Disperse at high speed for 35 min at 1200 r / min and 65-70 °C to make the dispersion fineness of the mixture no greater than 30 μm.

[0079] Reduce the material temperature to 50℃ and the dispersion speed to 500r / min. Add 4.0 parts of capsaicin slow-release granules and stir for 25min.

[0080] Lower the material temperature to below 45℃, then add 26.0 parts of diethyltoluene diamine, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 1.1 parts of activated 3A molecular sieve powder in sequence, and continue stirring at a speed of 500 r / min for 30 min.

[0081] Degassing was performed for 20 minutes under a vacuum of -0.09 MPa. The vacuum was then released using dry nitrogen, and the mixture was filtered through a 120-mesh sieve before being sealed and filled into containers to obtain component B of Example 2. Example 2 used the same component A as Example 1, and the coating was prepared according to the substrate treatment, spraying, and curing methods described in Example 1. The dry film thickness of the polyurea functional coating was controlled to be 2.0–2.5 mm.

[0082] In Example 2, the amount of terminal amino polysiloxane added was reduced to 6.0 parts, and the amount of capsaicin slow-release particles added was reduced to 4.0 parts, while the content of difunctional terminal amino polyether and diethyltoluene diamine was increased. The higher content of difunctional terminal amino polyether is beneficial to improving the integrity of the polyurea continuous phase, so that the coating maintains better elasticity, elongation at break, and adhesion to the primer.

[0083] Although the number of silicon-containing low surface energy regions and capsaicin slow-release units formed in Example 2 is lower than that in Example 1, it is still possible to form a functional structure that combines low surface energy desorption and natural active inhibition. Example 2 reduces the amount of terminal amino polysiloxane and capsaicin slow-release particles used, which helps to reduce the cost of functional raw materials and is suitable for ship hull surfaces with high seawater flow velocity, marine buoys, and tidal energy devices that can utilize water flow shear to promote the detachment of attached materials.

[0084] Example 3 According to the mass fraction, component B of this embodiment includes 40.0 parts of difunctional amino-terminated polyether, 7.0 parts of trifunctional amino-terminated polyether, 24.0 parts of diethyltoluene diamine, 10.0 parts of amino-terminated polysiloxane, 8.0 parts of capsaicin sustained-release granules, 5.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.0 part of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 1.1 parts of activated 3A molecular sieve powder, with a total mass fraction of 100 parts.

[0085] The difunctional and trifunctional amino-terminated polyethers were dehydrated at 80°C and under a vacuum of -0.09 MPa for 60 min to reduce the moisture content of both amino-terminated polyethers to less than 0.05%.

[0086] Add 40.0 parts of dehydrated difunctional amino-terminated polyether and 7.0 parts of dehydrated trifunctional amino-terminated polyether to a dispersion vessel, control the material temperature at 70℃, and stir at 400r / min for 10min.

[0087] The 10.0 parts of amino-terminated polysiloxane were divided into three equal portions and added sequentially. After each portion was added, the mixture was stirred at 500 rpm for 5 minutes before adding the next portion. After all the amino-terminated polysiloxane had been added, the mixture was stirred at 500 rpm for 25 minutes to reduce the possibility of phase separation caused by excessively high local concentrations.

[0088] Add 1.0 part of polymeric dispersant and continue stirring for 10 min. Then add 5.0 parts of rutile titanium dioxide and 1.5 parts of hydrophobic fumed silica in sequence. Disperse at high speed for 35 min at 1200 r / min and 65-70℃ to make the dispersion fineness of the mixture no greater than 30 μm.

[0089] Reduce the material temperature to 48-50℃ and the dispersion speed to 450 r / min. Divide 8.0 parts of capsaicin sustained-release granules into two equal parts, each part being 4.0 parts; after adding the first part, stir for 10 minutes, then add the second part, and continue stirring for 30 minutes after adding all the granules to reduce the damage to the sustained-release layer caused by collisions between the higher content sustained-release granules.

[0090] Lower the material temperature to below 45℃, then add 24.0 parts of diethyltoluene diamine, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 1.1 parts of activated 3A molecular sieve powder in sequence, and continue stirring at a speed of 500 r / min for 30 min.

[0091] The mixture was degassed for 25 minutes under a vacuum of -0.09 MPa, then the vacuum was released using dry nitrogen. After filtration through a 120-mesh filter, it was sealed and filled to obtain component B of Example 3. Example 3 used the same component A as Example 1, and prepared the coating according to the substrate treatment method and spraying method described in Example 1. The dry film thickness of the polyurea functional coating was controlled to be 2.2–2.8 mm.

[0092] In Example 3, the amount of terminal amino polysiloxane added was increased to 10.0 parts, which resulted in the formation of more silicon-containing low surface energy segments in the polyurea coating; the amount of capsaicin slow-release particles added was increased to 8.0 parts, which resulted in the formation of more capsaicin storage units within the coating per unit volume.

[0093] In Example 3, the amount of trifunctional terminal amino polyether added was increased to 7.0 parts to compensate for the potential decrease in the strength of the polyurea continuous phase caused by the increased addition of terminal amino polysiloxane and capsaicin sustained-release particles. The branched crosslinked structure formed by the trifunctional terminal amino polyether can improve the bonding strength of the polyurea matrix around the sustained-release particles and reduce the possibility of the sustained-release particles detaching from the coating during long-term seawater immersion and water flow erosion.

[0094] Example 3 is applicable to fixed components of marine platforms, port structures, seawater intake facilities, and marine aquaculture equipment that are in static or low-velocity seawater environments for extended periods.

[0095] Comparative Example 1 This comparative example was used to verify the effect of terminal amino polysiloxanes on the low surface energy properties of the coating and the desorption performance of marine fouling substances. By mass, component B of this comparative example included 51.0 parts of difunctional terminal amino polyether, 6.0 parts of trifunctional terminal amino polyether, 25.0 parts of diethyltoluene diamine, 6.0 parts of capsaicin slow-release particles, 6.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.2 parts of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder, totaling 100 parts by mass.

[0096] Compared to Example 1, this comparative example did not include terminal amino polysiloxane, and the amount of difunctional terminal amino polyether added was increased from 43.0 parts to 51.0 parts to compensate for the missing terminal amino polysiloxane by an equal mass. Except for the above component adjustments, the other raw materials, A component formulation, B component preparation method, substrate treatment method, spraying conditions, and curing conditions of this comparative example were the same as those in Example 1.

[0097] The coating formed in this comparative example mainly consists of a polyurea crosslinking network formed by terminal amino polyethers, diethyltoluene diamine, and isocyanate. Due to the absence of terminal amino polysiloxanes, stable silicon-containing low surface energy regions are not easily formed on the outer surface of the coating. Although capsaicin slow-release particles can still inhibit early colonization of marine organisms, the bonding strength between the marine organisms and the conventional polyurea surface is relatively high after the formation of the attachment.

[0098] Comparative Example 2 This comparative example was used to verify the effects of capsaicin slow-release particles on early biofilm formation and static marine antifouling performance. By weight, component B of this comparative example included 49.0 parts of difunctional amino-terminated polyether, 6.0 parts of trifunctional amino-terminated polyether, 25.0 parts of diethyltoluene diamine, 8.0 parts of amino-terminated polysiloxane, 6.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.2 parts of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder, totaling 100 parts by weight.

[0099] Compared to Example 1, this comparative example did not include capsaicin sustained-release particles, and the amount of difunctional terminal amino polyether added was increased from 43.0 parts to 49.0 parts to compensate for the missing capsaicin sustained-release particles by an equal mass. Except for the above component adjustments, the other raw materials, component A formulation, component B preparation method, substrate treatment method, spraying conditions, and curing conditions of this comparative example were the same as those in Example 1.

[0100] This comparative example retains the terminal amino polysiloxane, thus allowing the formation of a silicon-containing, low-surface-energy region on the outer surface of the coating. However, this comparative example does not contain capsaicin slow-release particles, preventing the formation of a sustained-action region of natural capsaicin at the interface between the coating and seawater. Under conditions of still or low-flowing seawater, bacteria and microalgae may still gradually form a biofilm on the coating surface.

[0101] Comparative Example 3 This comparative example was used to verify the effect of the composite sustained-release structure formed by porous silica loading and ethyl cellulose external coating on the release stability of capsaicin. By weight, component B of this comparative example included 43.0 parts of difunctional amino-terminated polyether, 6.0 parts of trifunctional amino-terminated polyether, 25.0 parts of diethyltoluene diamine, 8.0 parts of amino-terminated polysiloxane, 1.8 parts of capsaicin, 3.6 parts of porous silica, 0.6 parts of ethyl cellulose, 6.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.2 parts of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder, totaling 100 parts by weight.

[0102] In this comparative example, the total amount of capsaicin, porous silica, and ethyl cellulose added, as well as the mass ratio among them, are the same as the 6.0 parts of capsaicin sustained-release granules in Example 1. However, capsaicin sustained-release granules are not prepared in advance. Instead, capsaicin, porous silica, and ethyl cellulose are added directly to component B as independent raw materials.

[0103] The amino-terminated polyether, amino-terminated polysiloxane, rutile titanium dioxide, and hydrophobic fumed silica were mixed and dispersed according to the method in Example 1. The material temperature was reduced to 50°C and the rotation speed was reduced to 500 r / min. 3.6 parts of porous silica, 0.6 parts of ethyl cellulose, and 1.8 parts of capsaicin were added sequentially, and the mixture was stirred for 25 min. After adding the remaining raw materials, the mixture was mixed, vacuum degassed, filtered, and filled according to the method in Example 1.

[0104] In this comparative example, the capsaicin was not vacuum impregnated, and therefore did not pre-enter the internal pores of the porous silica; ethyl cellulose was also not pre-coated on the outside of the capsaicin-loaded porous silica. The three components did not form a composite particle structure of "capsaicin loaded internally and ethyl cellulose slow-release layer externally," meaning that free capsaicin easily migrated into the seawater quickly when the coating was first introduced into the seawater.

[0105] Comparative Example 4 This comparative example is used to verify the effect of terminal amino polysiloxanes, after being chemically fixed to a polyurea crosslinking network, on the long-term low surface energy performance and seawater stability of the coating. By weight, component B of this comparative example includes 43.0 parts of difunctional terminal amino polyether, 6.0 parts of trifunctional terminal amino polyether, 25.0 parts of diethyltoluene diamine, 8.0 parts of non-reactive dimethyl silicone oil, 6.0 parts of capsaicin slow-release particles, 6.0 parts of rutile titanium dioxide, 1.5 parts of hydrophobic fumed silica, 1.0 part of ultraviolet absorber, 0.7 parts of hindered amine light stabilizer, 1.2 parts of polymeric dispersant, 0.3 parts of silicone-free defoamer, 0.4 parts of polyether-modified silicone leveling agent, and 0.9 parts of activated 3A molecular sieve powder, totaling 100 parts by weight.

[0106] Compared to Example 1, this comparative example replaces 8.0 parts by mass of terminal amino polysiloxane with 8.0 parts by mass of non-reactive dimethyl silicone oil with a similar viscosity grade. The non-reactive dimethyl silicone oil does not contain terminal amino groups capable of rapidly reacting with isocyanate groups. Except for the above substitution, all other raw materials, component A formulation, component B preparation method, substrate treatment, spraying conditions, and curing conditions in this comparative example are the same as in Example 1.

[0107] Non-reactive dimethyl silicone oil can migrate to the outer surface of the polyurea coating during the curing process, thus generating a certain degree of low surface energy in the initial stage. However, since it is not chemically bonded to the polyurea crosslinking network, it tends to continuously migrate to the outside of the coating and gradually run off under long-term seawater immersion, water erosion, and temperature changes.

[0108] Performance testing methods Adhesion strength test: The adhesion strength between the coating and the substrate is tested using the pull-off method. At least three parallel samples are used in each group, and the average adhesion strength is calculated. After the test, the location of coating failure is observed.

[0109] Impact performance test: A 500g hammer is dropped freely from a height of 50cm onto the coating surface. After the impact, observe whether the coating cracks, peels, delaminates, or exposes the substrate.

[0110] Seawater resistance test: The coating sample was completely immersed in artificial seawater. After soaking for 40 days, 80 days and 120 days, the sample was taken out, the surface of the sample was rinsed with clean water, and the coating was observed to see if blistering, cracking, peeling, obvious loss of gloss and corrosion of the substrate occurred.

[0111] Surface wetting performance test: The static water contact angle of the outer surface of the coating was tested after 7 days of curing. The coating samples were immersed in artificial seawater for 30 days, 60 days and 120 days respectively. After reaching the corresponding immersion time, the static water contact angle was tested again and the water contact angle retention rate was calculated.

[0112] Capsaicin release performance test: Samples with the same area and coating thickness were immersed in artificial seawater of the same volume. Seawater samples were collected at 1d, 7d, 30d, 60d, 90d and 120d. The capsaicin content in the water samples was determined by high performance liquid chromatography and the cumulative capsaicin release rate was calculated based on the initial amount of capsaicin added.

[0113] Marine siding antifouling test: Marine siding samples of the same size were prepared from Examples 1-3 and Comparative Examples 1-4 and installed in the same sea area, at the same water depth, and facing the same direction. Observations and photographs were taken after immersion in seawater for 3, 6, 9, and 12 months. Image analysis methods were used to calculate the area of ​​seaweed, barnacles, shellfish, and other marine organisms attached to the coating surface. After rinsing with clean water at the same flow rate, the ease with which the attached organisms detached from the coating surface was evaluated.

[0114] Performance test results of the examples and comparative examples All embodiments and comparative examples used carbon steel substrates of the same specifications, and employed the same sandblasting treatment, primer type, spraying equipment, spraying pressure, and curing conditions. Except for Example 3, the dry film thickness of the polyurea functional coating in all groups of samples was controlled to be 2.0–2.5 mm; the dry film thickness in Example 3 was controlled to be 2.2–2.8 mm. The test results are shown in Table 1.

[0115] As shown in Table 1, the pull-out adhesion strength of Example 1 is 7.2 MPa. No cracks or peeling occurred under the 50 kg·cm impact condition. No blistering, cracking or substrate corrosion occurred after immersion in artificial seawater for 120 days. This indicates that the addition of amino-terminated polysiloxane and capsaicin slow-release particles did not significantly damage the continuous structure of the polyurea coating.

[0116] The initial static water contact angle in Example 1 was 109.6°, and after 120 days of immersion in artificial seawater, the water contact angle was 105.1°, with a water contact angle retention rate of 95.9%. The cumulative release rates of capsaicin after immersion in artificial seawater for 7, 30, and 90 days in Example 1 were 16.8%, 31.7%, and 55.4%, respectively, indicating a relatively gradual release process. After a 12-month marine sling test, the marine biofilm coverage was 3.6%, and after rinsing with clean water at the same flow rate, the residual attachment area decreased to 0.7%.

[0117] The pull-off adhesion strength of Example 2 was 7.6 MPa, higher than that of Examples 1 and 3. This is because Example 2 had a higher amount of difunctional terminal amino-terminated polyether and a lower amount of terminal amino-terminated polysiloxane and capsaicin slow-release particles, resulting in higher integrity of the polyurea continuous phase. After a 12-month marine biofilm test, Example 2 showed a marine biofilm coverage of 5.9%, making it suitable for scenarios requiring a combination of coating mechanical properties, production costs, and antifouling performance under dynamic water flow conditions.

[0118] The initial static water contact angle of Example 3 was 114.8°, and the water contact angle after 120 days of immersion in artificial seawater was 109.2°. After a 12-month marine biofilm test, the marine biofilm coverage was 2.4%, and the residual biofilm area after rinsing with clean water was 0.4%. In Example 3, the addition of terminal amino polysiloxane and capsaicin slow-release particles was relatively high, forming more silicon-containing low surface energy regions and natural active substance storage units, thus exhibiting strong static anti-biofilm adhesion capabilities.

[0119] Comparative Example 1, without the addition of terminal amino polysiloxane, had an initial static water contact angle of 86.7°. After a 12-month marine biofilm test, the marine biofilm coverage was 18.6%, and the residual attachment area after rinsing with clean water was still 9.8%. This indicates that capsaicin slow-release particles can retain a certain initial adsorption effect, but without a silicon-containing low surface energy area, the existing marine fouling is not easily removed by the water flow.

[0120] Comparative Example 2, without the addition of capsaicin slow-release particles, had an initial static water contact angle of 110.3°, which decreased to 105.8% after 120 days of immersion in artificial seawater, indicating that the amino-terminated polysiloxane could still form a relatively stable low surface energy region. However, after 12 months of marine biofilm formation testing, the marine biofilm coverage of Comparative Example 2 was only 25.3%, suggesting that the absence of capsaicin slow-release particles reduced the coating's ability to inhibit early biofilm formation and initial marine colonization.

[0121] Although the proportions of capsaicin, porous silica, and ethyl cellulose in Comparative Example 3 were the same as in Example 1, the three materials were not subjected to vacuum impregnation loading and external coating treatment. The cumulative release rates of capsaicin after 7 days, 30 days, and 90 days of immersion were 35.6%, 62.8%, and 82.6%, respectively, significantly higher than in Example 1, indicating that free capsaicin easily migrates rapidly into seawater in the early stages of coating application. After 12 months of marine biomass coverage in Comparative Example 3, the biomass coverage was 14.7%, indicating that the composite slow-release structure formed by the internal loading of porous silica and the external coating of ethyl cellulose is beneficial for prolonging the action time of capsaicin.

[0122] Comparative Example 4 used non-reactive dimethyl silicone oil to replace amino-terminated polysiloxane. Its initial static water contact angle was 113.9°, but after 120 days of immersion in artificial seawater, it decreased to 92.7°, with a water contact angle retention rate of 81.4%. This indicates that although non-reactive dimethyl silicone oil can improve the hydrophobicity of the coating in the initial stage, it is not chemically bonded to the polyurea crosslinking network, resulting in a weak ability to retain low surface energy properties after long-term seawater immersion.

[0123] In summary, the results show that amino-terminated polysiloxanes primarily reduce the adhesion strength between marine fouling materials and the coating by forming stable, low-surface-energy silicon-containing regions, and promote the detachment of adhering materials under water rinsing. Capsaicin-releasing particles primarily reduce the initial colonization tendency of bacterial biofilms, algal spores, and marine larvae on the coating surface by continuously releasing capsaicin. When both are added to the polyurea coating, they can simultaneously reduce initial marine biofilm attachment and decrease the adhesion strength between existing adhering materials and the coating. Example 1 demonstrates a good balance between adhesion strength, impact resistance, seawater resistance, low surface energy, capsaicin release stability, and long-term antifouling performance.

[0124] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. An environmentally friendly coating that prevents marine organism attachment, characterized in that, It includes components A and B, which are stored independently of each other; component A includes isocyanate-terminated polyether prepolymer and isocyanate trimer; Component B comprises difunctional amino-terminated polyether, trifunctional amino-terminated polyether, aromatic diamine chain extender, amino-terminated polysiloxane, capsaicin sustained-release particles, inorganic reinforcing filler, and functional additives; the capsaicin sustained-release particles comprise porous silica, capsaicin loaded within the pores of the porous silica, and an ethyl cellulose sustained-release layer coating the outside of the capsaicin-loaded porous silica. After the components A and B are mixed and cured, a polyurea crosslinking network is formed. The terminal amino groups in the terminal amino polysiloxane react with the isocyanate groups in the component A, so that the polysiloxane segments are linked to the polyurea crosslinking network through urea bonds, and a low surface energy region containing polysiloxane segments is formed on the coating surface. The capsaicin slow-release particles are dispersed in the polyurea crosslinking network, and the capsaicin is released slowly through the porous silica and ethyl cellulose slow-release layer.

2. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, Based on a total mass of 100 parts for component A, component A comprises 78-88 parts of isocyanate-terminated polyether prepolymer and 12-22 parts of hexamethylene diisocyanate trimer; based on a total mass of 100 parts for component B, component B comprises 40-46 parts of difunctional amino-terminated polyether, 4-8 parts of trifunctional amino-terminated polyether, 22-28 parts of aromatic diamine chain extender, 6-10 parts of amino-terminated polysiloxane, 4-8 parts of capsaicin sustained-release granules, 4-8 parts of rutile titanium dioxide, 1-2.5 parts of hydrophobic fumed silica, 0.5-1.5 parts of ultraviolet absorber, 0.3-1.0 parts of hindered amine light stabilizer, 0.5-1.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.2-0.6 parts of leveling agent, and 0.5-1.5 parts of activated 3A molecular sieve powder.

3. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, The isocyanate-terminated polyether prepolymer is an aliphatic isocyanate-terminated polyether prepolymer, and the isocyanate group mass content of the aliphatic isocyanate-terminated polyether prepolymer is 10.5% to 12.5%; the isocyanate trimer is a hexamethylene diisocyanate trimer, and the isocyanate group mass content of the hexamethylene diisocyanate trimer is 21% to 23%; the isocyanate group mass content of component A is 13.2% to 14.0%.

4. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, The terminal amino polysiloxane is α,ω-diaminopropyl-terminated polydimethylsiloxane, the number average molecular weight of the terminal amino polysiloxane is 1500-3000, and the amine value is 35-70 mgKOH / g; the terminal amino polysiloxane reacts with isocyanate groups at both ends of its amino groups to fix the polysiloxane segments in the polyurea crosslinking network.

5. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, Based on the total mass of the capsaicin sustained-release particles, the capsaicin sustained-release particles comprise 25%–35% capsaicin, 55%–65% porous silica, and 8%–12% ethyl cellulose; the capsaicin has a mass purity of not less than 95%, the porous silica has an average particle size of 5–15 μm, and the capsaicin sustained-release particles have a particle size of 5–20 μm.

6. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, The difunctional terminal amino polyether has a number-average molecular weight of 1800–2200 and an amine functionality of 2; the trifunctional terminal amino polyether has a number-average molecular weight of 4500–5500 and an amine functionality of 3; the aromatic diamine chain extender is diethyltoluene diamine; the inorganic reinforcing filler includes surface-treated rutile titanium dioxide and fumed silica treated with organosilane hydrophobicity.

7. The environmentally friendly coating that prevents marine organism adhesion according to claim 1, characterized in that, The isocyanate index of the mixture of component A and component B is 1.00 to 1.08; the cured coating includes a polyurea host layer connected to the substrate and a low surface energy functional region formed on the outside of the polyurea host layer, the capsaicin slow-release particles are dispersed in the polyurea host layer, and at least a portion of the capsaicin slow-release particles are located on the side close to the low surface energy functional region.

8. A method for preparing an environmentally friendly coating that prevents marine organism attachment as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. The isocyanate-terminated polyether prepolymer is added to the reaction equipment, heated and stirred under nitrogen protection, the isocyanate trimer is added, and after mixing, vacuum degassing and filtration are performed to obtain component A. S2. Vacuum dehydrate the difunctional amino-terminated polyether and the trifunctional amino-terminated polyether, mix the dehydrated difunctional amino-terminated polyether and trifunctional amino-terminated polyether, and add amino-terminated polysiloxane. S3. Add dispersant, rutile titanium dioxide and hydrophobic fumed silica to the mixture obtained in step S2, and disperse at high speed. S4. Reduce the temperature and dispersion speed of the material obtained in step S3, add capsaicin slow-release granules and disperse at low speed. S5. Add aromatic diamine chain extender, ultraviolet absorber, hindered amine light stabilizer, defoamer, leveling agent and activated 3A molecular sieve powder, mix, vacuum degas, filter and seal and fill to obtain component B; S6. Mix the components A and B and spray them onto the surface of the substrate. After curing, the environmentally friendly coating that prevents marine organisms from adhering is formed.

9. The method for preparing the environmentally friendly, anti-marine organism coating according to claim 8, characterized in that, The preparation method of the capsaicin sustained-release granules includes the following steps: dissolving capsaicin in ethanol, adding porous silica and pre-dispersing it; placing the mixture containing capsaicin and porous silica under a vacuum of -0.08 to -0.095 MPa for 20 to 40 minutes, releasing the vacuum and continuing to stir to allow capsaicin to enter and adsorb into the internal pores of the porous silica; removing ethanol under reduced pressure at 45 to 55°C to obtain capsaicin-loaded porous silica; dissolving ethyl cellulose in an organic solvent to form an ethyl cellulose coating solution; spraying the ethyl cellulose coating solution onto the surface of the capsaicin-loaded porous silica, and after mixing, vacuum drying and sieving, obtaining the capsaicin sustained-release granules.

10. The method for preparing the environmentally friendly, anti-marine organism coating according to claim 8, characterized in that, In step S6, the substrate is sandblasted to remove rust, achieving a surface cleanliness of Sa2.5, and an epoxy primer layer with a dry film thickness of 100–150 μm is formed on the substrate surface. Component A is heated to 65–75°C, and component B is heated to 60–70°C. The coating is then applied using a two-component high-pressure spraying device at a pressure of 14–20 MPa, with a volume ratio of component A to component B of 1:1 ± 0.

03. The resulting polyurea functional coating has a dry film thickness of 1.5–3.0 mm and is cured at 20–30°C for 24–36 hours.